Rhenium anodic dissolution in water-free methanol at different electrochemical parameters - E. N. Pryamilova; O. V. Chernyshova; D. V. Drobot (Тонкие химические технологии)
The process of rhenium anodic dissolution in methanol in the presence of lithium chloride was investigated. The unique construction of an electrochemical sell, firmware and the experimental technique for the investigation of anodic dissolution of rhenium and other d-elements in the water-free alcohols ROH (R = Me, Et, i-Pr, etc.), enabling to control and maintain constant potential (or current, if required), as well as to control in situ the concentration of the metal against the process duration were developed and introduced into the research process. A possible mechanism, by which rhenium derivatives are formed, was suggested.